ACCOUNTING OF TRANSACTION COST: ESSENCE, CLASSIFICATION, AND PROBLEMS OF REFLECTION IN ACCOUNTING - Chernenko, Kseniia; Salyha, Oleksandr (Current Problems of Sustainable Development, 2026)
The article examines the theoretical and methodological foundations of transaction cost accounting as a specific category of expenses that reflects the costs of organizing, supporting, and controlling economic relations between business entities. It reveals the economic nature of transaction costs, systematizes approaches to their classification, and identifies the features of information generation about them within the accounting system. The study substantiates that, at the current stage, the absence of a unified methodological approach to the identification, grouping, and disclosure of transaction costs complicates the completeness and reliability of accounting information. The article emphasizes the need to improve the accounting and analytical support for managing such costs in order to enhance the transparency of business processes and the soundness of managerial decisions.
Keywords: transaction costs, accounting, cost classification, accounting and analytical support, financial information, managerial decisions